Comparing Students’ Learning Outcomes Between the Question Student Have and Giving Question and Getting Answer Strategies in Grade VII Social Studies at SMP Negeri 20 Bengkulu - Jek Prengki; Adisel Adisel; Sepri Yunarman (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
This study aimed to examine whether there were differences in students’ learning outcomes between those who applied the Question Student Have strategy (questions from students) and those who applied the Giving Question and Getting Answer strategy (giving questions and receiving answers) in Social Studies learning in Grade VII at SMP Negeri 20 Bengkulu City. This experimental study used a comparative quantitative approach with a dual-paradigm research design involving two independent variables and one dependent variable. The population consisted of Grade VII students of SMP Negeri 20 Bengkulu City in the 2024–2025 academic year, while the sample comprised Class VII A as the experimental class and Class VII B as the control class. The research instrument was a Social Studies achievement test. The data were analyzed using a normality test, a homogeneity test, and a t-test. The results indicated differences in students’ learning outcomes between those using the Question Student Have strategy (questions from students) and those using the Giving Question and Getting Answer strategy (giving questions and receiving answers) in Social Studies in Grade VII at SMP Negeri 20 Bengkulu City. This was evidenced by the t-test results (tcount > ttable = 2.578 > 1.697) or p < 0.05 (i.e., 0.029 < 0.05), meaning that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected.